Warrant Financing - Stone, Bernell K. (Journal of Financial and Quantitative Analysis, 1976)
This article develops a criterion for comparing warrant financing with further common stock financing from the viewpoint of a firm's current stockholders. This criterion is then related to a complementary one presented by Bierman [1] and a condition is imposed on Bierman's cost of warrant financing for warrant financing to be preferred to further stock financing. Finally the article considers the limitations of these criteria and qualitatively discusses risk considerations that influence the attractiveness of warrant financing.